PROGRAM APPLICATION CALCULATIONS SPT PPH ARTICLE 21 IN SUCOFINDO COMPANY BANDUNG - Yosep Efendi; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2004)
This application program created to accelerate the computation time in data processing PPh Ps 21 that must be paid to the Tax Office. The proposed application can further simplify the preparation of reports to the Tax Office. This application program is expected to address problems related to data processing income tax calculation Ps 21.